Philosophical Postulates for an Education in Rousseau (Research, Society and Development, 2019)
The educational object that follows is a review of the book Rousseau and the Education postulated for a philosophy of education in which it defends that to man there is the possibility of being a free agent and that this only and possible through education. The review is organized in 7 topics: the world of Rousseau;  The meaning (s) of education; The three educations-or the masters of Rousseau; The education of Emilio; And Sofia, the education of women; Knowledge of pedagogical theory; Rousseau and Latin American education, which compose the book.